Promoting Forest City Management Based On Islamic Approach - Mikhriani; Luthfi Maulana; Imam Nawawi (Islamic Studies Journal for Social Transformation, 2019)
There are many Koranic verses revealed the structure of city space, including forest city itself.These verses confirmed the ancient history records that human being creates the greatcivilization. One of their prestigious creations is a modern management concept ofstructuring the forest city. It shows how to build a green space, an unpolluted air and water,and a healthy environment. This paper studied the Islamic approach to forest citymanagement in light a concept of Maqasid al-Syariah of Abu Ishaq Asy-Syatibi. Maqasid alSyariah are Islamic pillars whose goal that is keeping sustainability, the existence andcontinuity of human life. It means that Islam has serious concern over good environmentand its impact on health and wellbeing. According to Islam, the destructive behaviors causedamage just toward a single part of the environment are as bad as those destruct all of it.Therefore, managing forest city as well as Koranic directions depicted within its verses is aduty of Muslim people and for both secular or Islamic government.